Nonoperative Management of Blunt Hepatic Trauma: Comparison of Level I and II Trauma Centers. Issue 4 (April 2023) - Lewis, Meghan; Jakob, Dominik A.; Benjamin, Elizabeth R.; Wong, Monica; Trust, Marc D.; Demetriades, Demetrios
Introduction: Most blunt liver injuries are treated with nonoperative management (NOM), and angiointervention (AI) has become a common adjunct. This study evaluated the use of AI, blood product utilization, pharmacological venous thromboembolic prophylaxis (VTEp), and outcomes in severe blunt liver trauma managed nonoperatively at level I versus II trauma centers. Methods: American College of Surgeons Trauma Quality Improvement Program (TQIP) study (2013-2016), including adult patients with severe blunt liver injuries (AIS score>/= 3) treated with NOM, was conducted. Epidemiological and clinical characteristics, severity of liver injury (AIS), use of AI, blood product utilization, and VTEp were collected. Outcomes included survival, complications, failure of NOM, blood product utilization, and length of stay (LOS). Results: Study included 2825 patients: 2230(78.9%) in level I and 595(21.1%) in level II centers. There was no difference in demographics, clinical presentation, or injury severity between centers. Angiointervention was used in 6.4% in level I and 7.2% in level II centers (P=.452). Level II centers were less likely to use LMWH for VTEp (.003). There was no difference in mortality or failure of NOM. In level II centers, there was a significantly higher 24-hour blood product utilization (PRBC P = .015 and platelets P = .002), longer ventilator days (P = .012), and longer ICU (P< .001) and hospital LOS (P = .024). The incidence of ventilator-associated pneumonia was significantly higher in level II centers (P = .003). Conclusion: Utilization of AI and NOM success rates is similar in level I and II centers. However, the early blood utilization, ventilator days, and VAP complications are significantly higher in level II centers.